3032 MKit: Pilot Results of Primary Prevention Sexual Violence WebApp. (27th March 2019) - Munro-Kramer, Michelle; Cannon, Lindsay; Bauermeister, Jose; Kusunoki, Yasamin; Ngo, Quyen; Stephenson, Rob
Abstract : OBJECTIVES/SPECIFIC AIMS: Sexual violence (SV) is a public health crisis. High rates of SV are observed among college-age youth, yet holistic interventions are currently lacking. The purpose of this study was to conduct a pilot feasibility and acceptability test of a WebApp, MKit, which translates a clinical life skills approach to influence the health and well-being of university students. METHODS/STUDY POPULATION: We randomized two residence halls at a public university in the Midwest into a control group (n=139) that received typical university programming around SV and healthy relationships, or an intervention group (n=122) receiving MKit and the usual SV programming. We used online surveys to assess acceptability, feasibility, and usability at 3- and 5-months. Focus groups were conducted with a subsample of participants at 5-months to further investigate safety. RESULTS/ANTICIPATED RESULTS: The mean number of uses of MKit was 2.84 in a 5-month period. The majority of intervention participants endorsed the acceptability and usability of MKit as easy to use, well integrated, accessible, and easy to learn quickly. There were no concerns regarding personal safety. DISCUSSION/SIGNIFICANCE OF IMPACT: MKit provides a promising resource platform to deliver messages regarding healthy relationships and SV within the university context. By delivering SV-related content through a holistic life skills approach, MKit may offer new opportunities to reach and engage a wide range of students on how to foster healthy relationships.